First Report of Colletotrichum fructicola Causing Anthracnose on Glycine max in China - Xu, Mengting (Plant disease, 2023)
Soybean (Glycine max L.) is one of the important oilseed and vegetable crop worldwide and provides the main source of vegetable oil and proteins for human and livestock (Hartman et al. 2011). In October 2021, approximately 35% of soybean pods suffered from anthracnose in the farmer's field in Chongzhou, Sichuan Province, China (103°40'12"E, 30°37'48"N), and the occurrence area accounted for about 3.3 hm2. Symptoms of soybean were characterized by yellow spots at the initial stage, gradually expanded into dark brown spots, and eventually amounts of small black particles were densely arranged in the wheel shape on dead spots. Diseased spots of soybean pods were cut into pieces and sequentially sterilized in 75% alcohol for 30 s, 4% sodium hypochlorite for 30 s, sterile water for 3 times. After that, these pieces were placed on potato dextrose agar (PDA), and incubated at 25±2°C in the dark for 5-7 days. Single spore was separately picked and transferred to a fresh PDA plate to obtain pure culture isolates. Total six pure isolates were collected, and among them the hyphae of representative isolate 8-B were initially white, turned grey gradually on PDA medium, and the colonial reverse were radiating, whorled or a mixture of both. Conidia of 8-B were septate, hyaline, unicellular, cylindrical, obtusely rounded at both ends with 1 or 2 oil balls inside, and 10.5-17.6 µm in length and 7.0 µm-3.6 µm in width (n=100). The conidial appressoria were brown subspherical, 6.9 µm-13.3 µm in length and 5.6 µm-10.1 µm (n=50) in width. Based on morphological and cultural characteristics, the isolate 8-B was tentatively identified as Colletotrichum gloeosporioides species complex（Weir et al. 2012). To test pathogenicity, the mycelial plugs were inoculated on 20 detached soybean pods at full seed (R6) stage, and three areas of each pod were lightly scratched using a needle prior to inoculation. As controls, the PDA plugs were attached to the pinned-treated pods. Three independent replicates were conducted for control and inoculated pods, respectively. All pods were incubated in a greenhouse at 25 ± 2°C with a relative humidity of approximately 90%. After 4-5 days post-inoculation, typical anthracnose lesions were observed on the inoculated pods while the control pods remained healthy only with small wound spots. The pathogen re-isolated from all the inoculated pods were morphologically identical to the inoculation isolate (8-B). For further molecular verification, the six gene fragments including the internal transcribed spacer (ITS), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), chitin synthase 1 (CHS-1), actin (ACT), β-tubulin 2 (TUB2) and calmodulin (CAL) were amplified and sequenced (Weir et al. 2012, Damm et al. 2012), and the obtained sequences were deposited in GenBank (Accession numbers ON960278, ON685214, ON964475, ON974476, ON685215 and ON964477, respectively). All six gene sequences of 8-B had a high identity to C. fructicola (the stand isolate ICMP 18581) with the accession numbers ON960278 (100%), ON974476 (96%), ON685214 (99%), ON964475 (99%), ON685215 (100%), and ON964477 100%), respectively. Anthracnose disease caused by C. fructicola has previously been reported to affect a range of plant hosts worldwide (Guarnaccia et al. 2017). However, it is still unknown on C. fructicola causing anthracnose in soybean in China. This study firstly reports C. fructicola as the causal agent of anthracnose on soybean in the country, and provides a theoretical basis for the diagnosis and control of this disease